Sterile debates and dubious generalisations: An empirical critique of European integration theory based on the integration processes in telecommunications and electricity - Susanne K. Schmidt (Max-Planck-Institut für Gesellschaftsforschung, 1996)
Analyses of European integration processes are still dominated by the dichotomous debate between intergovernmentalism and supranationalism. Sides are often taken in this debate based on very case-specific empirical findings. An analysis of two cases, European telecommunications and electricity policy, illustrates how misleading such generalisations can be. The former case is often used to support supranational claims, while the latter highlights the importance of intergovernmental vetos. However, further analysis reveals the very parallel supranational policy approach of the European Commission to both sectors and the resulting weakness of the dominant interpretation. An analysis using a multilevel governance approach to European integration would avoid these difficulties. – – Viele Analysen des europäischen Integrationsprozesses orientieren sich an der Theoriedebatte zwischen intergouvernementalen und supranationalen Ansätzen. Häufig fußen Stellungnahmen jedoch auf empirischen Einzelfällen, die solch weitergehende Generalisierungen kaum zulassen. Eine Analyse der europäischen Telekommunikations- und Elektrizitätspolitik dient als Basis dieser Kritik. Erstere wird oft zur Unterstützung supranationaler Erklärungsansätze herangezogen, währenddessen der zweite Fall die fortwährende Dominanz intergouvernementaler Vetos hervorhebt. Die nähere Analyse zeigt jedoch, daß diese Interpretation zu kurz greift, denn in beiden Fällen verfolgte die Europäische Kommission einen parallelen, supranationalen Politikansatz. Eine Erklärung beiderFälle mit dem Ansatz europäischer Mehrebenenpolitik vermiede diese Probleme.
Keywords: 300